2017
DOI: 10.1186/s13104-017-2635-4
|View full text |Cite
|
Sign up to set email alerts
|

Endobronchial embolization for life-threatening hemoptysis with Endobronchial Watanabe Spigot

Abstract: BackgroundMassive hemoptysis is a common encounter in respiratory medicine. Bronchoscopy plays an important role in localizing the origin of bleeding, as well as endoscopic treatment of centrally located lesions. Endobronchial embolization is a novel technique enabling the management of hemoptysis arising even from peripheral lesions, via occlusion of the culprit bronchus, thereby securing the airway. Endobronchial Watanabe Spigot had been advocate in the treatment of bronchopleural fistula and the use of this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 9 publications
(12 reference statements)
0
11
0
Order By: Relevance
“…Bronchoscopy under general anaesthesia may be necessary when high volume active bleeding and hypoxaemia are concerns. Rigid bronchoscopy can be useful in this population by stabilising the airway, providing the possibility to use large bore suction and allowing endoscopic interventions such as the use of laser or argon and the positioning of oxidised regenerated cellulose [ 21 ], biocompatible glue [ 24 ], endobronchial stents [ 25 ] or silicone spigots [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Bronchoscopy under general anaesthesia may be necessary when high volume active bleeding and hypoxaemia are concerns. Rigid bronchoscopy can be useful in this population by stabilising the airway, providing the possibility to use large bore suction and allowing endoscopic interventions such as the use of laser or argon and the positioning of oxidised regenerated cellulose [ 21 ], biocompatible glue [ 24 ], endobronchial stents [ 25 ] or silicone spigots [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Silicone spigots, originally used in the treatment of bronchopleural fistula, have proved to be effective for temporary control of bleeding from segmental bronchi, allowing patients to stabilize before Bae. 53 When all the above devices are unable to stop bleeding, isolation of the healthy lung is the last chance. it can be achieved by selective intubation with a double-lumen endotracheal tube (carlens e robershow); the main disadvantage is technical difficulty in properly positioning.…”
Section: Procedural Stepsmentioning
confidence: 99%
“…Bronchial occlusion using EWS is performed to control any hemorrhaging from peripheral lung lesions. The data and clinical findings of previous reports and the present two cases of hemoptysis treated with bronchial occlusion using EWS are described in Table ( 7 - 12 ). In 2006, Dutau et al first reported a case of massive hemoptysis due to idiopathic bronchial hemorrhaging that was successfully treated with bronchial occlusion using EWS ( 7 ).…”
Section: Discussionmentioning
confidence: 89%
“…Bronchial occlusion using EWS can be applied for persistent air leaks in pneumothorax, postoperative or traumatic lung fistula, empyema with fistula, and fistula with other organs ( 6 ). Recently, the efficacy of bronchial occlusion using EWS for hemostasis has been reported ( 7 - 12 ). This procedure is usually performed for temporary hemostasis in conjunction with additional treatment methods, such as surgery and bronchial pulmonary embolization (BAE); however, both the long-term efficacy and safety of this method remain unclear.…”
Section: Introductionmentioning
confidence: 99%